Toxicological Impact of Lambda-Cyhalothrin on Apis Mellifera: Comparative Analysis Under Semi-Field and Field Conditions - Waseem, Mohammad Abdul; Thakur, Meena; Vallabuni, Sailaja; Sharma, Sunny; Hashem, Abeer; Abd Allah, Elsayed Fathi (Journal of Apicultural Science, 2024)
Lambda-cyhalothrin is the most widely used insecticide worldwide. This study investigates the impact of lambda-cyhalothrin on honeybees ( ) colonies under semi-field and field conditions utilizing the formulated product (Karate 5% at a concentration of 0.85 ml/l). Considering the application of lambda-cyhalothrin in onion fields, the foraging activities reduced by 27.89 and 29.28% under semi-field and field conditions, respectively. The number of dead workers in the comparison group was three-fold higher than that in the control group under both semi-field and field conditions. Under semi-field and field conditions, reductions were observed in the brood (22.6 and 24.01%), pollen (94.46 and 41.51%), and nectar (69.27 and 44.50%) areas. The effect of lambda-cyhalothrin on the strength of under semi-field conditions resulted in a significant decrease until the 14 day (2.20 bee frames/hive) and in field condition it was on the 7 day (4.79 bee frames/hive). This highlights the non-bee-safe nature of lambda-cyhalothrin when applied during flowering, and spraying should be avoided to reduce its contamination of nectar and pollen. Overall, our results show the significance of conducting field trials to accurately assess the risk of pesticides, depicting a more realistic exposure scenario under actual colony conditions.